Real-time-based E-health systems: design and implementation of a lightweight key management protocol for securing sensitive information of patients - Iqbal, Salman; Kiah, Miss Laiha Mat; Zaidan, A.A.; Zaidan, B.B.; Albahri, O.S.; Albahri, A.S.; Alsalem, M.A. (Springer, 2019)
Group-based systems, such as e-health systems, have been introduced since the last few decades. E-health systems can be used anytime and anywhere for patient monitoring. Wireless networks are continuously used to monitor patients’ conditions and recovery progress. The confidentiality, integrity and authenticity of patients’ health records are important to secure in such applications. Efficient key management and distribution are required to secure e-health applications in a wireless mobile environment. However, existing key management protocols cannot route e-health applications securely due to the resource-constrained architecture of the wireless mobile environment. A novel and enhanced key management scheme which aims to identify the challenges related to the security and privacy issues of patients’ sensitive information through a strong encryption management is proposed in this study. The proposed model also aims to provide a well-organised and lightweight key management mechanism. This system requires few computations of keys and offers a null rekeying mechanism to ensure forward and backward secrecies. As a result, a secure and privacy-preserving key management scheme for e-health systems, which is known as the healthcare key management (HCKM) framework and aims to decrypt the ciphertext of the same plain text with different keys, is acquired. HCKM minimises the rekeying overhead of group members and the overhead expressed in terms of the number of exchanged messages whilst achieving a sufficiently high security level. The proposed protocol also can operate on dynamic scenarios with a large number (thousands) of nodes and exhibits an excellent performance under the assumption of low rate of evictions. © 2018, IUPESM and Springer-Verlag GmbH Germany, part of Springer Nature.